(untitled) (El-Wahat Journal for Research and Studies, 2020)
This Study Attempts To Explain The Importance Of Linguistic Theory In The Process Of Analysis Of Letters And Accountability Of Literary Texts, And The Impact Of The Application Of The Achievements Of The Linguistic Lesson And Its Theories On Literary Discourse. The Research Necessitated The Procedures Of The Semiotic Theory - Especially The Cymbals Of Culture - In Line With The Nature Of The Study Model, Chicks; Because Of The Cultural Phenomena Embodied Behind The Text. The Semiotic Approach Seems To Be Important, Through Which We Can Understand The Cultural Systems And Meanings Employed By The Poet Through The Language, The Mediator That Takes A Qualitative Character Through Writing And Its Question Between The Act And The Interaction. It May Have Been Confined To The Structural And The Substitution, To Identify The Cultural Phenomena Found In The Said Text, Which May Have Been Behind The Motives Of Its Authorship. The Study Is Based On The Semiautomatic Approach At The Levels Of Analysis, Especially The Procedures Of The Semantics Of Culture, Because The Aim Behind This Is To Stand At The Most Important Cultural Phenomena Woven In The Text As A Written Proof Of Achievement. Keywords- Poem / Writing / Semiotics / Culture / Discourse